Carbimazole/methimazole embryopathy in siblings: A possible genetic susceptibility. Issue 11 (6th November 2013) - Goel, Himanshu; Dudding, Tracy
<x xml:space="preserve">Abstract</x> BACKGROUND The teratogenic effects of antenatal exposure of antithyroid drugs, carbimazole and methimazole have been well reported in the literature. These comprise of typical facial features and a wide variety of malformations such as choanal atresia, tracheo‐esophageal anomalies, congenital heart disease and ectodermal defects. However, the longitudinal studies have failed to establish the consistent teratogenicity of these drugs. CASES we report here two siblings with physical features consistent with carbimazole/methimazole embryopathy. We also describe previously unreported minor dental anomalies in these siblings with antenatal exposure of carbimazole. CONCLUSION Generally, only a small proportion of prenatally exposed children have the typical manifestations, and the presence in siblings supports a possible hereditary susceptibility to carbimazole/ methimazole embryopathy. This highlights the importance of recognizing this diagnosis before a subsequent pregnancy. Birth Defects Research (Part A) 97:755–758, 2013. © 2013 Wiley Periodicals, Inc.